2004
DOI: 10.1016/j.jconhyd.2003.07.001
|View full text |Cite
|
Sign up to set email alerts
|

Transport of radon gas into a tunnel at Yucca Mountain—estimating large-scale fractured tuff hydraulic properties and implications for the operation of the ventilation system

Abstract: Radon gas concentrations have been monitored as part of the operation of a tunnel (the Exploratory Studies Facility-ESF) at Yucca Mountain to ensure worker safety. The objective of this study was to examine the potential use of the radon data to estimate large-scale formation properties of fractured tuffs. This objective was examined by developing a numerical model, based upon the characteristics of the ESF and the Topopah Spring welded (TSw) tuff unit, capable of predicting radon concentrations for prescribed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 17 publications
1
10
0
Order By: Relevance
“…For example, transient changes in radon concentration can be used to assess the efficiency of mechanical ventilation (Unger et al, 2004). Transient changes of carbon dioxide concentration associated with anthropogenic sources can be another method to estimate natural ventilation and to model air exchanges patterns in underground cavities (Faimon et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…For example, transient changes in radon concentration can be used to assess the efficiency of mechanical ventilation (Unger et al, 2004). Transient changes of carbon dioxide concentration associated with anthropogenic sources can be another method to estimate natural ventilation and to model air exchanges patterns in underground cavities (Faimon et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…222 Rn concentrations in cave air vary from hundreds to thousands of Bq m À3 (Papachristodoulou et al, 2004 and references therein). Elevated concentrations of 222 Rn (up to 65,000 Bq m À3 ) were measured in the ESF air during periods without ventilation (Unger et al, 2004).…”
Section: Comparison Of Radon-produced Excess 206 Pb In Calcite From Ymentioning
confidence: 99%
“…Both types of data have been applied to characterizing the Yucca Mountain site, with the air‐ k tests extremely valuable for calculating fracture permeability within a small‐scale (∼1 m) spatial domain (Huang et al, 1999). In addition, Unger et al (2004) reported on an indirect approach of using radon gas concentration data, measured in an underground tunnel at Yucca Mountain, to estimate large‐scale fracture properties. It should be mentioned, however, that the application of subsurface pneumatic responses to surface barometric signals is in most cases limited to one‐dimensional vertical flow scenarios (Weeks, 1987; Ahlers et al, 1999; Neeper, 2002).…”
mentioning
confidence: 99%